Neonatal hypoxia: impacts on the developing mind and brain - Nafiseh Shabani; Alice Mado Proverbio; Alice Mado Proverbio (Frontiers in Cognition)
This review examines the cognitive, emotional, and neurofunctional effects of neonatal hypoxia in both the short and long term. Neonatal hypoxic-ischemic encephalopathy (NHIE) is a critical condition with profound and lasting effects on brain development and function. This mini review examines the structural, cognitive, behavioral, and psychopathological outcomes associated with NHIE, highlighting its impact on neurodevelopment. NHIE is linked to structural abnormalities such as reduced white matter integrity, ventricular enlargement, and damage to key regions including the basal ganglia, hippocampus, and corpus callosum. These changes correlate with long-term impairments in cognition, memory, and motor skills, alongside elevated risks of neurodevelopmental disorders such as autism spectrum disorder (ASD) and attention deficit/hyperactivity disorder (ADHD). Behavioral and emotional challenges, including anxiety, depression, and mood instability, are also prevalent. This review underscores the significant and multifaceted impact of NHIE on neurodevelopmental and behavioral health, emphasizing the importance of developing methodologies to eliminate or minimize neonatal hypoxic states as much as possible.